Do soil and water conservation practices influence crop productivity and household welfare? Evidence from rural Nigeria - Ogunniyi, A.I.; Omotayo, A.O.; Olagunju, K.O.; Motunrayo, O.; Awotide, B.A.; Mavrotas, G.; Aremu, A.O. (Springer, 2023)
One of the most serious challenges threatening agricultural sustainability in Nigeria is land degradation. Although this issue has received little attention, soil and water conservation practices have been identified as a possible pathway out of the potential problems posed by land degradation. Therefore, the central research question that this paper tries to address is the following: Do adoption of soil and water conservation (SWC) practices affect crop productivity and household welfare? This paper uses data collected by the International Institute of Tropical Agriculture (IITA) from maize farmers in rural Nigeria. We usedemploy the propensity score matching (PSM), inverse probability weighting adjusted regression model (IPWRA) approach, and the linear regression with endogenous treatment effect (LRETE) model to incorporate the typologies of SWC practices, and tested how the model affects crop productivity and household welfare. Additionally, multinomial logit was used to estimate the factors influencing the decision to adopt single and multiple SWC practices. The estimates show that education, age of the household head, access to credit, experience of drought, soil fertility, and occupational stress contribute to the decision to adopt SWC practices. The casual effect estimates reveal that both single and multiple adoptions of SWC practices had a positive and significant relationship with the crop productivity and welfare of the adopters. The results show that the adoption of combined SWC practices has a higher impact on crop productivity and welfare than single SWC practices. For instance, the adoption of a combination of three SWC practices was found to increase crop productivity and household welfare by 27.55% and 38.23%, respectively versus 13.91% and 15.11% in the case of single SWC practices. The study suggests that profile-raising agenda and efforts that focus on promoting the adoption of combination of SWC practices should be designed and implemented to enhance crop productivity and hence the welfare of the maize farming households in rural Nigeria.